Implementation of data intelligence models coupled with ensemble machine learning for prediction of water quality index - Abba S.I.; Pham Q.B.; Saini G.; Linh N.T.T.; Ahmed A.N.; Mohajane M.; Khaledian M.; Abdulkadir R.A.; Bach Q.-V. (Springer Science and Business Media Deutschland GmbH, 2023)
ammonia; artificial neural network; back propagation; biochemical oxygen demand; dissolved oxygen; nonlinearity; parameterization; prediction; regression analysis; water quality; India; Yamuna River; fuzzy logic; India; intelligence; machine learning; river; water quality; Fuzzy Logic; India; Intelligence; Machine Learning; Rivers; Water Quality